Caracterização tridimensional da região do Campo de Búzios usando análise multi-atributos sísmicos e dados de poços revela implicações sobre sua evolução tectono-estratigráfica - Fernanda Moura Costa (2023)
The Búzios Field is one of the most prolific petroleum fields along the Eastern Brazilian Margin. Despite significant research conducted restrictedly on the pre-salt reservoirs, few studies have focused on the three-dimensional characterization of the entire Búzios Field area. Therefore this work aims to spatially characterize a volume along the Búzios Field area using 3D seismic volume interpretation, seismic attributes, and well-log data. The combined use of these tools allowed the understanding of several parameters concerning the tectonostratigraphic evolution of the Santos Basin. Within the mapped area, we identified five units: Syn-Rift I, SynRift II, Post-Rift I, Post-Rift II, Drift I, and Drift II. The 3D model reveals significant features such as the depth variation of the Syn-Rift I unit and the heetrogeneous morphology of the PostRift II unit. The Syn-Rift I unit is deeper towards the N-NW and shallower towards the S-SE due to a regional half-grabens system. This system impacts the pre-salt geometry and thickness, as structural highs and lows are relevant factors in sediment accommodation. The Post-Rift I unit has a predominantly regular geometry and thickness but tends to thicken towards the S-SE and exhibits slight downward flexure towards the NE in the southeast of the Búzios Field. In three dimensions, the heterogeneous morphology of the Post-Rift II unit is evidenced by the variable thickness and irregular topography, accounting for the intense halokinesis in the Santos Basin. Above the evaporitic layer, the thickness of the Drift I unit is highly conditioned by salt morphology, with thicker and deformed packages in areas of thinner salt section. On the other hand, the Drift II unit shows relatively constant thickness with minor variations near fault zones. Comparisons with other fields within the Santos Basin (Tupi and Sapinhoá/Lapa) reveal differences in layer thickness, mobilization, and rotation of the syn-rift blocks. The Post-Rift I layer (Barra Velha Fm.) and the Post-Rift II package (Ariri Fm.) are thinner and less mobilized in the Búzios Field area. Moreover, the syn-rift blocks are less rotated, and the internal reflectors have a lower inclination in the study area when compared to these other fields. Therefore, this research concludes that the lower mobilization of salt, the lower thickness of the post-rift package, and the minor syn-rift block rotation observed in the Búzios Field area are associated with the relative distance from the continental margin and, consequently, with the amount of displacement generated by the South Atlantic Rift. In this case, the Búzios Field is located in a more proximal portion than Tupi and Sapinhoá/Lapa fields, exhibiting features suggestive of a lower displacement.